An ethnobotanical survey of antidiabetic plants used by Hausa–Fulani tribes in Sokoto, Northwest Nigeria. (22nd August 2015) - Salihu Shinkafi, Tijjani; Bello, Lawali; Wara Hassan, Sanusi; Ali, Shakir
Abstract: Ethnopharmacological relevance: Sokoto is known for its diverse traditional medicinal wealth and international market of traditional medicines in Africa. However, information of the folk knowledge, especially for the treatment of diabetes, is not documented. Aim of the study: This survey identified and documented the information on traditional medicinal plants used by Hausa–Fulani community of Sokoto for the treatment of diabetes. Materials and method: Demographic data and information about the medicinal plants were collected via administration of semi-structured oral questionnaires. Willing herbal medical practitioners/traditional healers were interviewed. The medicinal plants mentioned by herbalists were collected and authenticated by a taxonomist and the voucher specimens were preserved. Results: Fifty one informants across the state divulged information on traditional medicinal plants and practices used in diabetes and revealed 54 species, belonging to 33 families, with Cassia sieberiana being cited the most (19 times) and ranked first (39%). Azadirachta indica, Ficus exasperata and Schwenckia americana ranked second (15%), each cited 8 times. Conclusion: The survey documented the rich wealth of knowledge and usage of plants for the treatment of diabetes in Sokoto. The paper will not only serve as a source of information but will also help to make the knowledge accessible for further drug screening and development, and at the same time underlines the need for biodiversity conservation of this traditional wealth.